The Role of the Public Sector in the Market Economies of Developing Asia : General Lessons for the Current Debt Strategy. (IMF Working Papers; Working Paper ;, 1988)
This paper pursues several objectives. First, it presents a sketch of a positive (or real-world) theory of public sector intervention. Second, it analyzes in some detail the activity of the public sector in nine market economies of developing Asia and relates this activity to the growth of the foreign debt of these countries. It is argued that the relatively good performance of those countries was achieved at considerable and growing costs, especially in terms of external debt accumulation. Finally, the paper uses the experience of the Asian countries to draw some general lessons for the current debt strategy.